A case report on phenobarbitone induced stevens-johnson syndrome: an alarming hypersensitivity reaction - Dhara R. Zankat; Haiya J. Sheth; Raju G. Chaudhary; Supriya D. Malhotra; Pankaj R. Patel (International Journal of Medical Research and Review, 2018)
Stevens-Johnson syndrome (SJS) is an Ig E mediated hypersensitivity reaction, sometimes complicated by ocular manifestations. Antiepileptics induced SJS is common with carbamazepine. Phenobarbitone is known to cause hypersensitivity reactions like mild to moderate rashes but not life-threatening reactions like SJS. We present a case report of an 18 years old female patient who presented with chief complaints of multiple, fluid-filled lesions associated with itching all over the body for 20 days and inability to open her eyes for 18 days. It had developed following ingestion of Tab. Phenobarbitone 30 mg orally BD for 15 days. She was diagnosed as a case of SJS and treated with parenteral followed by oral corticosteroids and antihistaminics and recovered over a span of 20 days. Causality was assessed as per WHO-UMC Causality Assessment criteria and Naranjo Scale. Main pathogenesis is apoptosis through an interaction between cell-surface death receptor like Fas and its receptive ligand or due to genetic deficiency. In case of aromatic anticonvulsants, cross reactivity is also suspected. Genetic studies and cross reactivity testing can help prevent further incidences in few.